Cardiovascular risk reduction with icosapent ethyl. (November 2019) - Patel, Parth N.; Patel, Siddharth M.; Bhatt, Deepak L.
Abstract : Purpose of review: Residual risk for atherosclerotic cardiovascular disease (ASCVD) persists even among patients with optimal low-density lipoprotein cholesterol (LDL-C) levels. Randomized trials attempting to modulate other lipids beyond LDL-C have failed to demonstrate significant reductions in ischemic events. Recent findings: Mounting evidence suggests that triglyceride elevation is an independent risk factor for ASCVD. Though trials of triglyceride-lowering therapy in the statin era have failed to provide protection from ASCVD events, subgroup analyses have revealed that those with the highest triglycerides at time of enrollment appeared to receive the greatest clinical benefit. REDUCE-IT was a trial that enrolled patients with high triglycerides despite having goal LDL-C levels on statin therapy. Treatment with icosapent ethyl, a highly purified omega-3 fatty acid (OM3FA), eicosapentaenoic acid ethyl ester, provided a 25% relative risk reduction for the primary composite cardiovascular endpoint (hazard ratio 0.75, 95% CI 0.68--0.83; P  = 0.00000001), as well as a 30% relative risk reduction in total ischemic events ( P  = 0.00000000036). Summary: Icosapent ethyl was rigorously shown to decrease residual risk for cardiovascular events, though the benefits seen were likely because of mechanisms beyond mere triglyceride lowering. Clinical application of icosapent ethyl in this cohort of patients with residual risk is urgently needed.